On the Notion "Restricted Linguistic Theory": Toward Error-Free Data in Linguistics - Miner, Kenneth L. (Kansas Working Papers in Linguistics, 1978)
This paper has to do with the dichotomy generalism vs. particu-larism in linguistics; that is, the distinction between "theoretical linguistics" and the actual study of languages. I will urge (a) that theoretical linguistics is generally working with data containing errors of fact or of perspective, (b) that this is not necessarily due to mere carelessness but inheres in the practice of theoretical lin-guistics itself, (c) that this fact overrides normal principles of theory reduction which otherwise would prohibit restricted linguistic theories2 in favor of general linguistic theories, (d) that general linguistic theories must be replaced by restricted linguistic theories if linguistic theories are to be constructed on the basis of error-free data, and (e) that the effect of this conclusion on the field ought to be to remove "theoretical linguistics"3 as an activity in-dependent of the actual study of languages.